Processed ship-based Navigation Data from the Amundsen Sea, Antarctica acquired during the Nathaniel B. Palmer expedition NBP0901 (2009) (IEDA: Marine-Geo Digital Library, 2009)
This data set was acquired with a ship-based Navigation system during Nathaniel B. Palmer expedition NBP0901 conducted in 2009 (Chief Scientist: Dr. Stan Jacobs). These data files are of MGDS:Nav format and include Primary Navigation data and were processed after data collection. Data were acquired as part of the project(s): Collaborative International Research: Amundsen Sea Influence on West Antarctic Ice Sheet Stability and Sea Level Rise, Shedding dynamic light on iron limitation: The interplay of iron limitation and dynamic irradiance conditions in governing the phytoplankton distribution in the Ross Sea, and Collaborative Research: Sampling the ocean - sea ice interaction in the Pacific center of the Antarctic Dipole, and funding was provided by NSF grant(s): OPP06-32282.